BookTube, Book Clubs and the Brave New World of Publishing - Tolstopyat, Natalia (Satura, 2018)
Electronic media have increasingly affected and transformed the landscape of reading experiences and the book-selling industry. The constant improvement of e-book technology and consistent increase of Internet accessibility have brought new opportunities for readers and publishers. Blogging, particularly video blogging (vlogging), has become an essential form of the media since the beginning of 2000. While the Internet is often blamed for a decline of literary sections across traditional media platforms (Briggs and Burke 300), it has also given way to online platforms such as YouTube, Instagram, and Twitter. Websites, such as YouTube, offer different ways of collaboration for individuals and businesses through active involvement with user generated content (UGC). Publishing is one of those business spheres that followed their target audience into new media and digital formats. BookTube is the online reading community based on YouTube, and the vloggers who upload bookthemed videos are called BookTubers. This article will describe structure and basic elements of the BookTube community using parallels between them and book clubs. As many BookTubers also share their content on Instagram, where the same community of book enthusiasts is called Bookstagram, this platform will also be referenced. For the sake of this article, the terms book club and reading groups are used interchangeably. Lastly, the partnership of publishers and BookTubers as active agents in the field of literary and cultural production will be examined.